2018
DOI: 10.12688/f1000research.12938.2
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia: Genetics, lipoprotein lipase and HindIII polymorphism

Abstract: The direct link between lipid metabolism alterations and the increase of cardiovascular risk are well documented. Dyslipidemias, including isolated high LDL-c or mixed dyslipidemia, such as those seen in diabetes (hypertriglyceridemia, high LDL-c or low HDL-c), correlate with a significant risk of cardiovascular and cerebrovascular disease worldwide.  This review analyzes the current knowledge concerning the genetic basis of lipid metabolism alterations, emphasizing lipoprotein lipase gene mutations and the Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…In contrast to these findings, Hall and colleagues found no ethnic variation in the frequencies of five common LPL gene mutations related to circulating TG levels (-93T/G, D9N, N291S, S447X, and the Hind III) 85 86 87 90 91 92 in individuals of South Asian, white European, and African descent 88 . However, no meaningful association of these mutations was observed with fasting TG concentrations.…”
Section: Lipoprotein Lipase Activitymentioning
confidence: 85%
“…In contrast to these findings, Hall and colleagues found no ethnic variation in the frequencies of five common LPL gene mutations related to circulating TG levels (-93T/G, D9N, N291S, S447X, and the Hind III) 85 86 87 90 91 92 in individuals of South Asian, white European, and African descent 88 . However, no meaningful association of these mutations was observed with fasting TG concentrations.…”
Section: Lipoprotein Lipase Activitymentioning
confidence: 85%
“…Notably, this is associated with low levels of plasma triglycerides and increases in HDL cholesterol in healthy subjects. However, in subjects with obesity, this allele instead is associated with elevated levels of plasma triglycerides ( Palacio-Rojas et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the pathogenesis involves an interaction between genetic, environmental and eventually epigenetic factors. Epigenetic factors, including microRNAs, not only represent a key for understanding the complexity of vascular diseases in these patients but also represent a new field of investigation to discover new diagnostic and prognostic markers ( 6 ).…”
Section: Introductionmentioning
confidence: 99%